Unveiling the determinants of financial reporting quality among ASEAN’s banks - Isabella, Tricia Jalleh; Peh, Jennifer Li Ying; Wong, Shi Ting; Ong, Pei Yi (2024)
This study delves into the intricate landscape of financial reporting quality among banks across the Asian region, examining the multifaceted determinants that influence the accuracy, transparency, and reliability of financial information disclosed by these institutions. Against the backdrop of increasing globalization and interconnected financial markets, the quality of financial reporting plays a pivotal role in fostering investor confidence, regulatory compliance, and overall economic stability. Therefore, this research aims to study the determinants of financial reporting quality among Asia’s banks. The secondary data was collected via ‘Refinitiv’ software and annual reports. There are 52 Asia’s banks being investigated by using simple random sampling under probability sampling. A software namely ‘Stata’ has been utilized to conduct the analysis. The outcome of the analysis shown that Female Director (FD), Audit (Big4), Dividend Payout Ratio (DPR), Net Margin Profitability (NetMarPr), GDP Growth (GDPgr), Inflation (Inflat), Corruption Perception Index (CPI) have significant effects on financial reporting quality, excluding Board of Directors (BoD), Years of Service (YoS), Size, Total Equity/Total Asset (TETA) which do not have a significant relationship with financial reporting quality. Thus, the findings offer practical insights for bank executives and policymakers seeking to enhance reporting practices, corporate governance frameworks, and regulatory oversight to bolster the credibility and reliability of financial information in the Asian banking sector. Keywords: Financial Reporting Quality, Board of Directors (BoD), Female Director (FD), Years of Service (YoS), Audit (Big4), Size, Total Equity/Total Asset (TETA), Dividend Payout Ratio (DPR), Net Margin Profitability (NetMarPr), GDP Growth (GDPgr), Inflation (Inflat), Corruption Perception Index (CPI